2003
DOI: 10.1128/aem.69.4.2276-2283.2003
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Rhizobial Genotypes within Natural Populations of Rhizobium leguminosarum Biovar viciae for Nodulation of Host Legumes

Abstract: Populations of Rhizobium leguminosarum biovar viciae were sampled from two bulk soils, rhizosphere, and nodules of host legumes, fava bean (Vicia faba) and pea (Pisum sativum) grown in the same soils. Additional populations nodulating peas, fava beans, and vetches (Vicia sativa) grown in other soils and fava beannodulating strains from various geographic sites were also analyzed. The rhizobia were characterized by repetitive extragenomic palindromic-PCR fingerprinting and/or PCR-restriction fragment length pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
172
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 53 publications
10
172
0
3
Order By: Relevance
“…The finding showed that strains isolated from vicieae tribe's cross-inoculation group were able to form nodules with faba bean plant but, the number, color, and shape of nodule varied according to the strain inoculated (Laguerre et al, 2003). Nodules produced by strain on one legumes host may have no resemblance to nodules produced by the same strain on another host in the same cross-inoculation group (Mahajan and Gupta, 2009) (Table 6).…”
Section: Cross-inoculation and Symbiotic Effectiveness Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding showed that strains isolated from vicieae tribe's cross-inoculation group were able to form nodules with faba bean plant but, the number, color, and shape of nodule varied according to the strain inoculated (Laguerre et al, 2003). Nodules produced by strain on one legumes host may have no resemblance to nodules produced by the same strain on another host in the same cross-inoculation group (Mahajan and Gupta, 2009) (Table 6).…”
Section: Cross-inoculation and Symbiotic Effectiveness Testmentioning
confidence: 99%
“…The finding showed that Rhizobia strain that is effective in nitrogen fixation in association with one plant species may also be effective with certain other legumes (Amara, 1990). This is demonstrated by isolates of pea and faba bean able to form nodules and fix nitrogen with faba bean host (Laguerre et al, 2003). However, due to the influence of host plant on diversity and the genetic structure, R. lguminosarum bv.viciae reflect differences in the degree of host specificity and effectiveness of nitrogen fixation within the viceae tribe cross-inoculation group (Handley et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGS III was predominant in both legumes and was distributed in all the treatments applied to cowpea and green gram. The dominance of indigenous strains can be attributed to a number of factors; the adaptability of indigenous rhizobia to their environment results in high levels of saprophytic competence (Zengeni et al 2006); build up of background strains in the presence of the host rhizosphere (Dowling and Broughton 1986;Bushby 1993;Mendes and Bottomley 1998) and the competitive ability of background strains for sites of infection on the host plant roots and nodulation (Laguerre et al 2003;Leite et al 2009). It is therefore imperative to consider how rhizobial populations in the soil can be manipulated to influence, with or without effectual inoculation, legume nodulation, N 2 fixation and plant productivity (Brockwell et al 1995;McInnes and Haq 2003).…”
mentioning
confidence: 99%
“…Negligible reports on the molecular diversity of rhizobia infecting legumes of Indian origin and particularly mungbean (Vigna radiata (L. Wilczek) are available [5]. Studies on the molecular diversity of root nodule bacteria in rhizosphere, soil or nodules have been conducted to properly classify these rhizobia and also to correlate with promiscuity, symbiotic properties, effectiveness and competitiveness of these bacteria in different legumes but no conclusion has been drawn fi nally [6][7][8][9][10]. There may be differences between the population densities of different strains in soil and these differences may infl uence the outcome of nodulation.…”
Section: Introductionmentioning
confidence: 99%